Invention, centralité et fin du travail - Michel Freyssenet † (Revue de la Régulation)
Work is not only a historically dated word or notion, but also an invented reality, constructed by the European 18th century. It corresponds to the emergence of the labour relationship and the ‘free’ worker selling his or her capability to work. Through its spread and progressive hegemony, this social relationship has become the reference to perceive, think and organize any other activity. The consequence has been an extension of the term ‘work’ to activities which no longer stem from the labour relationship, such as ‘domestic work’, ‘independent work’ and so on. Work has been ‘naturalized’ and ‘universalized’. This contemporary reality —originally geographically circumscribed— has been projected on the past and on other societies. We need to explain it through historical conditions that caused it to emerge three centuries ago. Nor has it been socially intrinsic from the outset, as it has become today by being the condition of access to resources necessary for life in our societies. If its historicity logically implies its disappearance one day, it cannot reasonably be prognosticated for the near future, as it supposes the marginalization of the social relationship which brought it forth.